(untitled) (The Review of Diabetic Studies, 2025)
Background: In global perspective, the prevalence of type 2 diabetes mellitus keeps increasing and rising in all regions. The occurrence of DM is invariably preceded by the occurrence of prediabetes. The increasing number of prediabetes cases and the resulting increase in the incidence of diabetes mellitus necessitate the efforts to prevent the occurrence of complications. One effort that can be made is to work up self-care behavior in people with prediabetes, one of which is through dalihan natolu counseling. Objective: This study aims at observing the efforts to improve prediabetes self-care using dalihan natolu counseling. Method: This study is a quantitative study with a nonequivalent control group quasi-experimental design with a sample size of 66 which consists of a control group and an intervention group. Data collection procedure was conducted using the Summary of Diabetes Self Care Activity (SDSCA) questionnaire with the recall method for the previous 7 days. The intervention carried out on the respondents in the intervention group was in the form of counseling and assistance by Dalihan Natolu for 3 months, which aimed to improve self-care for people with prediabetes. Data analysis was performed using a paired t-test for the intervention group and a Wilcoxon test for the control group. Further, a Mann-Whitney test was utilized to compare the control group and the intervention group. Findings: The Mann-Whitney test performed on the control and intervention groups yielded a p-value of 0.000, indicating that dalihan natolu counseling is effective in improving self-care behavior in people with prediabetes. Conclusion: Dalihan Natolu counseling is effective as the effort to improve self-care among people with prediabetes. This becomes a concrete example of transcultural nursing theory, which incorporates cultural and kinship elements into the process of caring for family members with prediabetes.